The relationship between ventricular size at 1 month and outcome at 2 years in infants less than 30 weeks' gestation. Issue 3 (9th January 2014) - Fox, Lisa M; Choo, Pauline; Rogerson, Sheryle R; Spittle, Alicia J; Anderson, Peter J; Doyle, Lex; Cheong, Jeanie L Y
Abstract : Background: Cranial ultrasound cerebral biometric measurements have been used in preterm neonates, particularly in cases of ventriculomegaly. While cerebral biometric measures using MRI have been found to correlate with long-term outcome, the relationship between cranial ultrasound biometric measures and neurodevelopmental outcome has not been established. Objective: To assess the relationship between ventricular size at 1 month of age using cranial ultrasound and neurodevelopmental outcome at 2 years in very preterm infants. Method: Digital cranial ultrasound images taken between 25 and 35 days of age of 44 infants born at less than 30 weeks' gestation were analysed independently by two observers. Infants with significant ultrasound abnormalities were excluded. A range of ultrasound linear measures were correlated with Bayley Scales of Infant and Toddler Development, Third Edition (Bayley-III) motor, language and cognitive composite scores at 2 years using linear regression. Results: Larger lateral ventricular sizes (anterior horn width, ventricular height, midbody ventricular height) and larger ventricular-brain biparietal ratios were related to poorer motor composite score at 2 years. A ventricular-brain ratio of less than 0.3 was reassuring with regard to motor outcome. Poorer language composite scores at 2 years were associated with larger midbody ventricular heights. There was little evidence of a relationship with the cognitive composite score. Conclusions: Larger lateral ventricles in the parietal region at a month of age were related to poorer motor development at 2 years. Larger ventricular measurements were also related to slower early language development. The role of cranial ultrasound biometric measures as biomarkers of later outcome in very preterm infants warrants further investigation.